2017
DOI: 10.4103/jfcm.jfcm_45_17
|View full text |Cite
|
Sign up to set email alerts
|

Are nurses verbally abused? A cross-sectional study of nurses at a university hospital, Eastern Province, Saudi Arabia

Abstract: BACKGROUND:Workplace violence against health-care workers is a significant problem worldwide. Nurses are at a higher risk of exposure to violence. Studies available in Saudi Arabia are few.OBJECTIVES:The objective of the study was to estimate the prevalence of verbal abuse of nurses at King Fahd Hospital of the University (KFHU) in Khobar, Saudi Arabia, and to identify consequences and the demographic and work-related characteristics associated with it.MATERIALS AND METHODS:This cross-sectional study of 391 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 27 publications
6
47
4
Order By: Relevance
“…Few other studies have examined this topic in Saudi Arabia, and the majority were conducted in hospitals. [14][15][16][17][18][19] A total of 47% of HCWs in this study experienced workplace violence during the 12-month period prior to our investigation. This is very similar to reports from a study conducted at family medicine centers in Riyadh (45.6%), but it substantially exceeds the rate reported in two other studies conducted in the Eastern Province, in Al Khobar (30.7%) and Alhassa (28%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few other studies have examined this topic in Saudi Arabia, and the majority were conducted in hospitals. [14][15][16][17][18][19] A total of 47% of HCWs in this study experienced workplace violence during the 12-month period prior to our investigation. This is very similar to reports from a study conducted at family medicine centers in Riyadh (45.6%), but it substantially exceeds the rate reported in two other studies conducted in the Eastern Province, in Al Khobar (30.7%) and Alhassa (28%).…”
Section: Discussionmentioning
confidence: 99%
“…16 A similar study was conducted at a university hospital in the Eastern Province in 2015 among 450 nurses, in which 30.7% reported experiencing verbal abuse in the 12-month period prior to the study. 17 A 2012 cross-sectional study conducted among 258 HCWs at two public hospitals in Riyadh showed that 67.4% had experienced violence during the 12-month period prior to study, 18 while a 2010 cross-sectional study conducted among 1091 HCWs in Al-Hassa City found that 28% had experienced at least one violent event during the previous year, the majority emotional/verbal abuse (92.1%) versus physical violence (7.9%). 19 When it comes to the risk factors of violence in healthcare settings, the abovementioned study in Spain found that violent events were caused by dissatisfaction with provided care (36.3%), wait times (17.0%), and pharmaceutical prescriptions (12.9%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method allowed the nurses to express their own experience through interviews. As a result, the lived experiences of this verbally abused nurses were revealed (Varga & Holloway, 2014;Al-Shamlan et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Workplace violence against healthcare professionals in the Middle East has been thoroughly studied recently. [16][17][18] Although government policies and regulations are in place, the rate of workplace violence in the Middle East, such as in Saudi Arabia, is quite high. 16 In Saudi Arabia, over twothirds of healthcare professionals have experienced some form of violence, from either patients or their families.…”
Section: Introductionmentioning
confidence: 99%